2021
DOI: 10.3390/microorganisms9010111
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Microbial Metal-Chelating Siderophores for the Removal of Metal Ions from Solutions

Abstract: To guarantee the supply of critical elements in the future, the development of new technologies is essential. Siderophores have high potential in the recovery and recycling of valuable metals due to their metal-chelating properties. Using the Chrome azurol S assay, 75 bacterial strains were screened to obtain a high-yield siderophore with the ability to complex valuable critical metal ions. The siderophore production of the four selected strains Nocardioides simplex 3E, Pseudomonas chlororaphis DSM 50083, Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…The intensity of the color zone was characteristic of the strain regardless of the metal present in the medium. This color change reaction could be most likely related to the chemical structure or concentration of the secreted siderophores (Koedam et al 1994 ; Milagres et al 1999 ), as well as acidification of the medium (Shin et al 2001 ; Hofmann et al 2021 ). According to scientific studies, the color of the observed zones can range from reddish-purple (Milagres et al 1999 ; Srivastava et al 2018 ), magenta (Srivastava et al 2018 ), orange (Milagres et al 1999 ; Shin et al 2001 ) to yellow and colorless (Patel et al 2018 ; Singh et al 2020 ; Hofmann et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the color zone was characteristic of the strain regardless of the metal present in the medium. This color change reaction could be most likely related to the chemical structure or concentration of the secreted siderophores (Koedam et al 1994 ; Milagres et al 1999 ), as well as acidification of the medium (Shin et al 2001 ; Hofmann et al 2021 ). According to scientific studies, the color of the observed zones can range from reddish-purple (Milagres et al 1999 ; Srivastava et al 2018 ), magenta (Srivastava et al 2018 ), orange (Milagres et al 1999 ; Shin et al 2001 ) to yellow and colorless (Patel et al 2018 ; Singh et al 2020 ; Hofmann et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these colors are indicative of specific class of siderophores. Blue agar is known to be discolored to pink by catechols and to orange by hydroxamates, while yellow halos (Hofmann et al 2021 ) can indicate the production of both siderophores and acidifying non-typical chelators such as citric and oxalic acids (Srivastava et al 2018 ). Observations of intermediate colors, between pink and orange, may be associated with the production of several types of siderophores by a strain.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophore-producing microbes produce siderophore and have activities of biofertilizers and bio-control for the plant; thus SPM acts as a signature for sustainable agriculture and is eco-friendly for crop production in degraded land Table 1 (Alam, 2014 ). Siderophore-producing microbes reduce Fe deficiency and enhance all physiological and biochemical processes of the plant under saline soil (Sultana et al, 2021 ), drought conditions (Kumar et al, 2016 ), and heavy metal-stressed soil (Hofmann et al, 2021 ). Siderophore also changes the oxidation states of heavy metals such as Cd, Cu, Ni, Pb, Zn, Th, U, and Pu and makes them less toxic (Schalk et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In agriculture and the environment, siderophores increase the growth and yield of various plants, woods, and textiles through the improvement in iron acquisition [24][25][26]. Moreover, hydroxamatetype siderophore plays an important role in immobilizing the metals in soil [22,27]. In biocontrol, siderophores are considered a growth inhibitor for various phytopathogenic fungi and toxic algal blooms [22,28].…”
Section: Introductionmentioning
confidence: 99%